POTRET PERGESERAN RELASI GENDER DAN DAMPAKNYA BAGI KELUARGA PEKERJA MIGRAN INDONESIA (PMI) (Martabat: Jurnal Perempuan dan Anak, 2020)
This article examines the shift in gender relations in the context of the families of Indonesian Migrant Workers (PMI). By taking an object in Rejotangan District as the most PMI area in Tulungagung Regency, this article uses a symbolic approach to attempts to portray the process of interaction between individuals in the context of PMI families. In this case, the concept of patriarchy is no longer valid. The husband begins to play a role in the domestic sector; cooking, taking care of children and doing everything about the household. While the wife, only has a role to fulfill the family’s living, whether as a housemaid, taking care of elderly parents, or in other sectors abroad. Such matter does not only have implications for material-economic factors but also psychologically and sociologically; there is a complexity of family problems whose impact can lead to the destruction of household relations and the education of their children.